2017
DOI: 10.1016/j.vaccine.2016.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination in people with type 2 diabetes, coverage, predictors of uptake, and perceptions. Result of the MADIABETES cohort a 7years follow up study

Abstract: The uptake of influenza vaccination among diabetic patients in the present study was below desirable levels. The main barrier to vaccination was lack of knowledge regarding the need for and risks and advantages of influenza vaccination. Healthcare professionals should educate and encourage influenza vaccination among people with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 31 publications
8
54
1
Order By: Relevance
“…Our results (Table 2) confirm that both modifiable (medical care) and nonmodifiable factors (aging and clinical deterioration) were associated with increased SIV uptake rates. 6,12,14,20 This finding is both intuitive and fortunate and helps to lighten, in part, the dark picture of low SIV coverage in patients with diabetes: low coverage involves, above all, patients with the least serious forms of disease. Our results suggest that any clinical encounter with patients with diabetes, both vaccinated and nonvaccinated, should be taken as a new opportunity to make them aware of the importance of SIV, especially when their diabetes is becoming more severe.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Our results (Table 2) confirm that both modifiable (medical care) and nonmodifiable factors (aging and clinical deterioration) were associated with increased SIV uptake rates. 6,12,14,20 This finding is both intuitive and fortunate and helps to lighten, in part, the dark picture of low SIV coverage in patients with diabetes: low coverage involves, above all, patients with the least serious forms of disease. Our results suggest that any clinical encounter with patients with diabetes, both vaccinated and nonvaccinated, should be taken as a new opportunity to make them aware of the importance of SIV, especially when their diabetes is becoming more severe.…”
Section: Discussionmentioning
confidence: 75%
“…These findings confirm the key role of doctors in promoting SIV among at-risk patients. 6,12,21 Previous studies have shown that patients trust their physicians strongly 7 and that these professionals can play an important role in improving patients' knowledge and decision-making process about SIV. 22,23 The absence of any similar effect for endocrinologists and cardiologists, however, suggests that these specialists might be missing some opportunities to promote SIV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deaths attributable to diabetes mellitus doubled in the 1990–2010 period and disability-adjusted life years increased by 30% 1 13–15. Since diabetes mellitus is one of the chronic conditions associated with a worsened outcome of influenza, international public health organisations (WHO and Centers for Disease Control and Prevention) and national and international diabetes associations recommend annual influenza vaccination for persons with diabetes mellitus 16…”
Section: Introductionmentioning
confidence: 99%